Pre-sentence reports. The effects of legislation and national standards - Cavadino, Michael (The British journal of criminology, 1997)
The Criminal Justice Act 1991 and the associated National Standards for the Supervision of Offenders in the Community (1992) replaced social inquiry reports' (SIRs) with new-style pre-sentence reports' (PSRs). This paper presents the results of a before-and-after study assessing the effects of the change on the reports themselves. Matched samples of SIRs from 1991 and PSRs from 1993, drawn from four separate court areas in the north of England and covering juveniles' reports provided by local authority social workers as well as probation officers, are compared for similarities and differences. The results show that there were highly significant differences between the SIRs and the PSRs, with the latter being much more likely to focus upon offending behaviour and discuss the seriousness of the offence. Report writers and sentencers were on the whole remarkably positive about the changes